Implementation of IoT for temperature monitoring system on combustion furnace - Prayoga, Noval; Risfendra (Journal of Industrial Automation and Electrical Engineering, 2025)
Combustion equipment requires precise and continuous temperature monitoring to ensure process safety and efficiency. Manual monitoring often causes delays and a lack of real-time feedback, which increases the risk of thermal instability. To address this issue, this study proposes an IoT-based temperature monitoring system that uses affordable and open-source components. The system uses an ESP32 microcontroller and a type K thermocouple for temperature measurement. Temperature data is transmitted via Wi-Fi to a PHP-based web server, stored in a MySQL database, and displayed in real-time through a remotely accessible web interface. The development method involved system design, sensor integration, microcontroller programming, and testing. Flowcharts and block diagrams were created to define the system's behavior. The system was evaluated through sensor accuracy testing, data verification, and latency measurements. The results showed that the sensor had an error margin of less than 5% compared to a gun thermometer. Data recorded by the ESP32 matches 100% with database and web outputs. Average data transmission delay is approximately 3 seconds, indicating responsive real-time monitoring. This system demonstrates a reliable, scalable, and cost-effective solution for industrial furnace monitoring, enhancing operational safety through IoT-based automation.